Structural Relationship among Mobile Phone Dependence, Self-Efficacy, Time Management Disposition, and Academic Procras-tination in College Students - PengSheng Chen (Tehran University of Medical Sciences, 2021)
Background: We aimed to investigate the relationship among mobile phone dependence, self-efficacy for self-regulated learning, time management disposition, and academic procrastination in Chinese students majoring in physical education. In addition, we explored the mediating roles of self-efficacy for self-regulated learning and time management disposition in the relationship between mobile phone dependence and academic procrastination.